2006
DOI: 10.1109/tnano.2005.858591
|View full text |Cite
|
Sign up to set email alerts
|

Organic thin-film transistors using pentacene and SiOC film

Abstract: Pentacene for organic thin-film transistors (OTFTs) was deposited on the SiOC film by thermal evaporation. The transfer characteristic of the pentacene channel as the active layer is dependent on the chemical properties of a surface-on-gate insulator. Hybrid-type SiOC film can have all chemical properties from organic to inorganic properties according to the deposition condition. Pentacene on SiOC film shows the gradient or normal growth because of the C=C bond in SiOC film. Normal growth of pentacene molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…This result was the same of IGZO reports as a previous paper [5]. However, to improve the transistor for transparent display applications, it is also necessary to develop the oxide semiconductor of p-type [7]. This work provides the correlation between the Schottky contact and PF contact in zinc oxide semiconductor transistor used on SiOC as a gate insulator.…”
Section: Introductionsupporting
confidence: 83%
“…This result was the same of IGZO reports as a previous paper [5]. However, to improve the transistor for transparent display applications, it is also necessary to develop the oxide semiconductor of p-type [7]. This work provides the correlation between the Schottky contact and PF contact in zinc oxide semiconductor transistor used on SiOC as a gate insulator.…”
Section: Introductionsupporting
confidence: 83%
“…These sites were recombined according to the balanced formation by the equilibrium of the repulsive and attractive forces during the deposition. The hydroxyl group was evaporated by the annealing and then decreased the dielectric constant of SiOC film [9]. They have been focused on the correlation between lowering the polarization and the reduction of the dielectric constant, but it is not clearly defined the effects about the ionic and electronic polarity witch is affected the reduction of the dielectric constant, respectively.…”
mentioning
confidence: 99%
“…It has been known that the dielectric constant of SiOC film fabricated by CVD (chemical vapor deposition) decreases as the polarization of the film lowers. Moreover, it has been reported that SiOC as a gate insulator improves the performance of TFT [12]. The electron emission of the defects resulting from the localized deep level states in semiconductor band gap is associated with the ionization energy of the localized state in dielectric materials.…”
Section: Introductionmentioning
confidence: 99%